A first-principles study of Sc-decorated graphene with pyridinic-N defects for hydrogen storage. (2nd February 2017) - Luo, Zhifen; Fan, Xiaoli; Pan, Rui; An, Yurong
Abstract: Introducing impurity atoms and vacancy prevents transition metal atoms from aggregating on carbon-based nanomaterials, which makes the TM decoration a realistic and effective way to improve the hydrogen storage capacity. By performing the first-principles calculation, we studied the adsorption of hydrogen molecules on Sc-decorated graphene with single-vacancy defect (SV) and pyridinic-N defects: SV + 1N, SV + 2N, SV + 3N and DV + 4N. Our calculations show that Sc atoms will be uniformly dispersed on these defective graphene with the binding energies higher than the cohesive energy of bulk Sc. We find that the binding energy of Sc and the adsorption energy of H2 molecules on these defective structures both change gradually as the variation of N concentration. The Sc-decorated SV + 3N is the most promising material for hydrogen storage, in which each Sc atom could store 5H2 with the adsorption energies in the range of 0.2–0.4 eV. Moreover, our calculations show that the double-sided Sc-decorated graphene with pyridinic-N defects can adsorb more H2 molecules with higher adsorption energies. It indicates that the double-sided adsorptions are more favorable for hydrogen storage with high capacity. Graphical abstract: Highlights: Vacancy and pyridinic-N defects prevent the clustering of Sc atoms on graphene. As the concentration of N dopants increases, the binding of Sc atom to the defective graphene weakens. The adsorption energy of H2 on the decorated Sc atom enhances as the increasing of the N-concentration. The Sc-decorated SV + 3N is the best candidate materials for hydrogen storage.